SAT-505 A Rare Case of Teriparatide Induced Persistent Hypercalcemia - Sistla, Divya (J Endocr Soc, 2019)
INTRODUCTION Teriparatide is a recombinant endogenous parathyroid hormone. It is an anabolic medication which is FDA approved for treating Osteoporosis in postmenopausal women, men with primary or hypogonadal osteoporosis and Glucocorticoid-induced osteoporosis. Transient hypercalcemia with Teriparatide is reported in 1-3% of patients, 4-6 hours after the dose administration and lasts for 24 hours. It is thought to be through the increased renal production of 1,25-dihydroxy vitamin D, increased intestinal calcium absorption and inhibition of renal calcium excretion. We report a case of persistent hypercalcemia with Teriparatide use. CASE REPORT: A 74-year-old Caucasian female presented to the hospital with mental status changes, generalized bone pain, weight loss, and poor oral intake. Her past medical history includes Rheumatoid arthritis, Sjogren syndrome, osteoporosis with compression fractures and osteoarthritis of multiple joints. Patient’s medications include Prednisone 5 mg daily, calcitonin nasal spray, vitamin D and calcium supplements. She had previously failed bisphosphonate therapy for osteoporosis. She developed new compression fracture of L4 vertebra while being treated with Denosumab. Hence Teriparatide was started 4 months prior and she received the last dose 3 days prior to the presentation On presentation, she was noted to have severe hypercalcemia with total calcium of 17.3 mg/dL, ionized calcium of 9.4 mg/dL, albumin of 3.2 g/dL and a suppressed PTH of 3ng/L. Laboratory workup including renal function, phosphorus level, 25-hydroxyvitamin D level, 1,25-dihydroxy vitamin D, Parathyroid hormone-related peptide, Thyroid stimulating hormone, serum, and urine protein electrophoresis was unremarkable. CT scan of the neck, chest, abdomen, and pelvis showed no mass lesions or lymphadenopathy. An extensive evaluation failed to identify other causes of hypercalcemia except for immobilization. She was treated as a new onset Non-PTH dependent severe Hypercalcemia case. The patient had multiple admissions with recurrent hypercalcemia since then despite discontinuation of Teriparatide. Her calcium level normalized transiently with Intravenous fluids, an Intravenous bisphosphonate, and calcitonin. However, such treatment failed to maintain normal calcium level for more than 3-4 weeks.DISCUSSION Recurrent severe hypercalcemia with Teriparatide use is rarely reported. Although immobilization can precipitate hypercalcemia, immobilization is rarely a sole etiology of severe hypercalcemia. Our case report suggests that severe recurrent hypercalcemia can be associated with teriparatide use especially in the setting of immobilization. As far as we are aware, this is the fourth reported case of persistent hypercalcemia with Teriparatide use. This case highlights the importance of monitoring calcium levels periodically when Teriparatide is used.